Literature Study: Sustainable Natural Resources Management as a Solution to Environmental Problems in Indonesia - Nida’ Farah Abiyya; Achmad Husen; Dian Alfia Purwandari; Hasnah Lidiawati; Fani Akmaliyah Safitri (Publikasi Indonesia, 2025)
Environmental problems in Indonesia, including deforestation, land degradation, water pollution, and biodiversity decline, present serious challenges to sustainable development. This study examines sustainable natural resource management as a solution through a comprehensive literature review. The findings reveal that participatory approaches, green technology implementation, and evidence-based policies can significantly reduce environmental degradation. The research highlights the crucial role of multi-stakeholder collaboration between government, private sector, and local communities in formulating effective sustainability policies. Importantly, the study demonstrates that integrating strict regulations with community empowerment and technological innovation offers the most promising path toward sustainable resource management. The research implications are threefold: First, it provides policymakers with a framework for developing integrated environmental policies. Second, it underscores the need for capacity building in local institutions to implement sustainable practices. Third, it identifies technology adoption as a critical factor for effective environmental monitoring. These findings contribute to ongoing discussions about sustainable development by offering practical solutions that balance economic growth with environmental preservation. The study concludes that a holistic approach combining policy reform, technological advancement, and community participation is essential for addressing Indonesia's environmental challenges while ensuring long-term sustainability.